Sejarah Branding Kuliner Halal di Kota Medan, 2003-2019 - Mariam, Siti; Rohani, Laila; Naldo, Jufri (Warisan: Journal of History and Cultural Heritage, 2023)
The concern surrounding halal and haram products is a focal point for legal scholars and historians, sparking ongoing debates within various societal sectors. This study delves into the historical evolution of halal branding within the culinary industry in Medan. Historical methods and qualitative approaches, encompassing literature reviews, observations, interviews, and documentation, were employed to gather data. Findings emphasize the pivotal role of halal branding in ensuring the safety, comfort, and availability of halal products, impacting the well-being of a diverse population. The journey began in 1976 with the introduction of a logo signifying the presence of pork, subsequently gaining momentum in 1988 when researchers from the University of Brawijaya Faculty of Enforcement identified food products suspected of pork content. A year later, the Indonesian Ulema Council (Majelis Ulama Indonesia - MUI) established the Food, Drug, and Cosmetics Assessment Institute (LPPOM) to oversee halal certification. The enactment of the Halal Product Assurance Law (UUJPH) in late 2014 mandated that all products circulating within Indonesia must hold halal certification, coinciding with the establishment of the Halal Product Assurance Agency (BPJPH) under the Ministry of Religious Affairs.